(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of Small-Sided Games (SSG) training on passing accuracy in futsal among players aged 13–15 years at Fafage Academy Sumedang. The main issue addressed in this research is the low passing accuracy among young players, which can negatively impact overall team performance. Small-Sided Games were selected as the training method because they involve fewer players in a smaller playing area, allowing for higher ball-touch frequency and decision-making under conditions that simulate real match situations. This research employed a quantitative method with a pretest-posttest experimental design. The sample consisted of 20 male futsal players aged 13–15 years who actively trained at Fafage Academy Sumedang. Data were collected through passing accuracy tests conducted before and after the intervention. Data analysis included normality, homogeneity, paired sample t-test, and R-Square tests using SPSS version 26. The results showed an increase in the mean score from 4.05 in the pre-test to 6.65 in the post-test. The paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant effect of SSG training on passing accuracy. The R-Square value indicated that the training contributed 24% to the improvement, while the remaining 76% was influenced by other factors. In conclusion, Small-Sided Games training proved to be effective in improving passing accuracy in futsal for adolescent players and is recommended as a practical approach in technical training programs for youth academies.